(untitled) (Research, Society and Development, 2022)
Edible films and coatings are designed to protect food, increasing its shelf life. They have the potential to reduce the use of traditional synthetic polymers and maintain food quality by controlling mass transfer and improving mechanical, physical, and chemical integrity. In addition to limiting respiration in vegetables, packaging can act against enzymatic browning, lipid oxidation reactions, and reduction in the growth of pathogenic microorganisms. Thus, the objective of the present work was to elaborate a systematic review on edible biodegradable films, considering the physical stability of filmogenic solutions for the production of edible films with antioxidant activity and their characterization regarding their physicochemical and technological properties. The research focused on articles published in the last ten years, starting in 2012. From the selected papers, the inputs used in the formulations of the films and coatings, the physical modifications promoted by each biopolymer, and what were the results obtained were evaluated. Biomaterials are presented as an alternative for reducing environmental impact, replacing conventional plastic packaging with edible films and coatings applied to food, or even as primary packaging. There are several options for biodegradable films and coatings on the market, and the initial barrier to commercial adoption has already been overcome. In this way, public policies and tax incentives are suggested to increase the use of biodegradable and edible packaging and intensify consumer education, encouraging the adoption of eco-friendly packaging.